Publicity in Conservation Programme in U.S.A. - Singh, Bharat; Sankhala, K. S. (Indian Forester, 1964)
The paper gives a brier account of the working of publicity sections and public relations programme of the various conservation services of the U.S. government with whom the authors had the opportunity to work during their study tour of that country.